2003
DOI: 10.1021/jp035375w
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Growth Model of Periodic Spindle-Unit BN Nanotubes by Nitriding Fe-B Nanoparticles with Nitrogen/Ammonia Mixture

Abstract: Periodic spindle-unit boron nitride (BN) nanotubes with buglelike open-end tips have been found in the product by nitriding Fe-B nanoparticles at 1100 °C with a mixture of nitrogen and ammonia gas. The microstructure was well-characterized by high-resolution transmission electron microscopy (HRTEM) and energy-dispersive X-ray spectroscopy (EDX). The diameter of this BN nanotube shows a decreasing tendency along the growth direction. For each spindle unit, the outer diameter decreases steeply and then increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 40 publications
2
29
1
Order By: Relevance
“…The molten catalyst is occasionally partially trapped inside the bamboo-like nanotubes as shown in Figure 8(a), and may be responsible for the formation of these nanostructures via an improved stress-induced sequential growth mechanism. The overall diameter of these nanotubes was found to be almost uniform throughout the length, and are different from spindle-like morphology observed by Huo et al [30] from the nitridation of Fe-B nanoparticles at 1100˚C in the presence of a mixture of nitrogen and ammonia where the tube diameter was found to decrease along the growth direction, although the growth mechanism for the formation of these defective BN nanostructures was al-most similar and follow the stress-induced sequential growth mechanism. Figure 8(c amined at higher magnification.…”
Section: Surface and Internal Morphologies Of Bn Nanostructurescontrasting
confidence: 89%
“…The molten catalyst is occasionally partially trapped inside the bamboo-like nanotubes as shown in Figure 8(a), and may be responsible for the formation of these nanostructures via an improved stress-induced sequential growth mechanism. The overall diameter of these nanotubes was found to be almost uniform throughout the length, and are different from spindle-like morphology observed by Huo et al [30] from the nitridation of Fe-B nanoparticles at 1100˚C in the presence of a mixture of nitrogen and ammonia where the tube diameter was found to decrease along the growth direction, although the growth mechanism for the formation of these defective BN nanostructures was al-most similar and follow the stress-induced sequential growth mechanism. Figure 8(c amined at higher magnification.…”
Section: Surface and Internal Morphologies Of Bn Nanostructurescontrasting
confidence: 89%
“…Therefore, there must be an alternative growth model. Furthermore, for the tubes formed in the conventional sequential growth model, the nanoparticles are not necessarily uniform in size if there is any inside the tubes, [11] but it is necessary for these nanoparticles to be located at the knobs if they appear. [9c,11] However, in our case, for a given tube, the size of nanoparticles is identical and individual nanoparticles can be occasionally found in the middle of YG units (refer to Fig.…”
Section: Growth Mechanismmentioning
confidence: 99%
“…To date, since the first observation of Bamboo-shaped BNNTs, [8] different morphologies of BNNTs and corresponding growth mechanisms have been reported. [9][10][11][12] However, metal nanoparticles periodically filled nanotubes have been rarely reported. [10][11][12] In this study, we demonstrate a simple method to synthesize yard-glass (YG) shaped BNNTs periodically filled with magnetic Fe nanoparticles using a floating catalyst method and such synthesized YG-BNNTs possess unique magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21) Huo suggested that the FeB nanoparticles should be in a molten or quasi-liquid state at 1373 K, which is lower temperature than the melting point of the bulk FeB, so that N atoms from the atmosphere easily diffuse into the FeB ''catalyst'', and when they become supersaturated, BN is precipitated in a solid state. As Fe-B compounds were generated in the process of the reaction between B andFe 2 O 3 , 12) it is considered that BN in the sample I was generated through the decomposition of Fe-B compounds, following the VLS mechanism.…”
Section: Discussionmentioning
confidence: 99%